Mesenchymal stem cell spheroids alleviate neuropathic pain by modulating chronic inflammatory response genes - Lee, Nayeon; Park, Gyu Tae; Lim, Jae Kyung; Choi, Eun Bae; Moon, Hye Ji; Kim, Dae Kyoung; Choi, Seong Min; Song, Young Cheol; Kim, Tae Kyun; Kim, Jae Ho (Frontiers in Immunology, 2022)
Chronic neuropathic pain is caused by dysfunction of the peripheral nerves associated with the somatosensory system. Mesenchymal stem cells (MSCs) have attracted attention as promising cell therapeutics for chronic pain; however, their clinical application has been hampered by the poor in vivo survival and low therapeutic efficacy of transplanted cells. Increasing evidence suggests enhanced therapeutic efficacy of spheroids formed by three-dimensional culture of MSCs. In the present study, we established a neuropathic pain murine model by inducing a chronic constriction injury through ligation of the right sciatic nerve and measured the therapeutic effects and survival efficacy of spheroids. Monolayer-cultured and spheroids were transplanted into the gastrocnemius muscle close to the damaged sciatic nerve. Transplantation of spheroids alleviated chronic pain more potently and exhibited prolonged in vivo survival compared to monolayer-cultured cells. Moreover, spheroids significantly reduced macrophage infiltration into the injured tissues. Interestingly, the expression of mouse-origin genes associated with inflammatory responses, Ccl11/Eotaxin, interleukin 1A, tumor necrosis factor B, and tumor necrosis factor, was significantly attenuated by the administration of spheroids compared to that of monolayer. These results suggest that MSC spheroids exhibit enhanced in vivo survival after cell transplantation and reduced the host inflammatory response through the regulation of main chronic inflammatory response-related genes.